The influence of hot dip galvanizing process on intermetallic phases formation. Issue 2 (15th February 2019) - Bellini, Costanzo; Iacoviello, Francesco; Carlino, Francesco; Di Cocco, Vittorio
Abstract: Cheaper metallic materials are susceptible to environmental corrosion due to low values of electrochemical potentials. For instance, low carbon steels, but recently ductile cast irons too, show many problems of mechanical properties degradation due to corrosion. Therefore, it is important to protect these alloys against corrosion for safety reasons by using low‐cost coating techniques like Hot Dip Galvanizing (HDG).